Genre in Hellenistic Poetry - Harder, M.A.; Regtuit, R.F.; Wakker, G.C. (Classical Studies - Book Archive pre-2000., 1998)
This volume contains the papers of the 'Groningen Workshops on Hellenistic Poetry 3. Genre in Hellenistic Poetry' held at Groningen from 28-31 August 1996. During the workshop a first draft of the papers, which were sent to the participants of the workshop in advance, was discussed and commented on by an international group of specialists in the field of Hellenistic poetry. The volume contains a wide range of articles and thus provides a survey of current developments in research on an important aspect of Hellenistic poetry. In the past the Hellenistic treatment of genre was often described as 'Kreuzung der Gattungen', but during the last decades the development of modern literary criticism and its influence on research in Hellenistic poetry has led scholars to more refined views and suggested new questions. The aim of this workshop was to summarize and reconsider the results of earlier scholarship and to embark on new or until now neglected aspects of genre in Hellenistic poetry.